2021
DOI: 10.1186/s12876-021-01604-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experiences and predictors of success of treatment with vedolizumab in IBD patients: a cohort study

Abstract: Background Vedolizumab has become a standard treatment for the inflammatory bowel diseases ulcerative colitis (UC) and Crohn’s disease (CD). However, there is an ongoing debate on the ideal individual treatment algorithms and means to predict treatment response are not routinely established. Aims We aimed to describe our experiences with vedolizumab at a large German tertiary referral center and to identify clinical predictors of success of vedoliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
5
5
0
Order By: Relevance
“…Since these data were only indicating relative expression and not absolute cell numbers, and did not exclude the possibility of coexpression of a4 and b7 integrin without heterodimerization, we seeked to validate our findings in an additional patient cohort. Here, we stained full blood samples and used fluorescently labeled vedolizumab, a monoclonal antibody specific for the a4b7 heterodimer used for the therapy of inflammatory bowel diseases (25). In accordance with previous literature marked lymphopenia was present in COVID-19 patients (Supplementary Figure 3).…”
Section: Results A4b7 Integrin-expressing Memory T Cells Are Decreasesupporting
confidence: 68%
“…Since these data were only indicating relative expression and not absolute cell numbers, and did not exclude the possibility of coexpression of a4 and b7 integrin without heterodimerization, we seeked to validate our findings in an additional patient cohort. Here, we stained full blood samples and used fluorescently labeled vedolizumab, a monoclonal antibody specific for the a4b7 heterodimer used for the therapy of inflammatory bowel diseases (25). In accordance with previous literature marked lymphopenia was present in COVID-19 patients (Supplementary Figure 3).…”
Section: Results A4b7 Integrin-expressing Memory T Cells Are Decreasesupporting
confidence: 68%
“… 23 Several studies have assessed endoscopic remission with VDZ; however, the timing of colonoscopic evaluation and remission rate (30–60%) varied among the studies. 24 , 25 , 26 , 27 In our study, the endoscopic remission rate at week 24 was 60.0% (21/35), similar to a previous report evaluating real‐world outcomes. 27 We observed that the cumulative VDZ administration continuation rate was significantly higher in patients who achieved endoscopic remission, and most of the patients in the non‐endoscopic remission group withdrew VDZ within the observation period.…”
Section: Discussionsupporting
confidence: 90%
“…Narula et al reported that achievement of MES of ≤1 was noted in 29% and 62% patients at week 24 and week 48, respectively, in the VICTORY study 23 . Several studies have assessed endoscopic remission with VDZ; however, the timing of colonoscopic evaluation and remission rate (30–60%) varied among the studies 24–27 . In our study, the endoscopic remission rate at week 24 was 60.0% (21/35), similar to a previous report evaluating real‐world outcomes 27 .…”
Section: Discussionsupporting
confidence: 88%
“…The complexity and heterogeneity of IBD has resulted in a difficult endeavor for the scientific community to attribute causality as well as in raising treatment efficacies above the current therapeutic ceiling marked by endoscopic remission rates of around 30% 27,28 although real world observations recorded slightly higher efficacy rates [29][30][31] . The current standard of care which includes histological examination (used currently only for diagnosis and not for therapeutic endpoints) following endoscopy does not capture the fine-prints of disease biology such as cellular heterogeneities, cell-type specific expression, interactions among cell-types and microbial influences.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity and heterogeneity of IBD has resulted in a difficult endeavour for the scientific community to attribute causality as well as to raise treatment efficacies above the current therapeutic ceiling marked by endoscopic remission rates of around 30%, 27 , 28 although real-world observations recorded slightly higher efficacy rates. 29–31 The current standard of care, which includes histological examination [used currently only for diagnosis and not for therapeutic endpoints] following endoscopy, does not capture the fine print of disease biology such as cellular heterogeneities, cell type-specific expression, interactions among cell-types, and microbial influences. In response new approaches, like systems biology which integrates high-throughput datasets profiling different layers of biological organisation and the network of molecular interactions, have often been suggested as the ‘holy grail’ for understanding and treating IBD as well as other complex diseases.…”
Section: Introductionmentioning
confidence: 99%